N-channel InGaAs field-effect transistors formed on germanium-on-insulator substrates - Ivana (2013)
InGaAs n-channel metal oxide semiconductor field-effect transistors (MOSFETs) were fabricated on germanium-on-insulator (GeOI) substrate for the first time. Integration of InGaAs on a GeOI substrate was achieved using a molecular beam epitaxy (MBE)-grown InAlAs graded buffer. The fabricated MOSFET, with a self-aligned Ni–InGaAs metallic source/drain, achieves good device characteristics. The normalized transconductance (Gm·tox) compares very well with reported data for InGaAs n-MOSFETs formed on bulk InP substrates, and is significantly higher than reported data for In0.53Ga0.47As n-MOSFETs fabricated on Si substrates using a similar growth technique.